2021
DOI: 10.1016/j.apsb.2020.09.008
|View full text |Cite|
|
Sign up to set email alerts
|

VEGFR2-targeted antibody fused with IFN mut regulates the tumor microenvironment of colorectal cancer and exhibits potent anti-tumor and anti-metastasis activity

Abstract: Although interferon α (IFN α ) and anti-angiogenesis antibodies have shown appropriate clinical benefit in the treatment of malignant cancer, they are deficient in clinical applications. Previously, we described an anti-vascular endothelial growth factor receptor 2 (VEGFR2)-IFN α fusion protein named JZA01, which showed increased in vivo half-life and reduced side effects compared with IFN α , and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Vascular endothelial growth factor (VEGF) and its receptors (VEGFR) are important regulators of angiogenesis and vascular permeability [100]. In sepsis-AKI mice, studies have shown that increased plasma VEGF levels and decreased local renal VEGFR expression cause decreased glomerular endothelial fenestrae density and increased systemic microvascular permeability, suggesting that VEGF-VEGFR are jointly involved in regulating endothelial injury after AKI [91,101].…”
Section: Endothelial Responsesmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) and its receptors (VEGFR) are important regulators of angiogenesis and vascular permeability [100]. In sepsis-AKI mice, studies have shown that increased plasma VEGF levels and decreased local renal VEGFR expression cause decreased glomerular endothelial fenestrae density and increased systemic microvascular permeability, suggesting that VEGF-VEGFR are jointly involved in regulating endothelial injury after AKI [91,101].…”
Section: Endothelial Responsesmentioning
confidence: 99%
“…However, the affinity of IFN-α2 for its receptor and its direct cytotoxicity were decreased in this combination. Thus, subsequent studies mutated IFN-α to further improve the anti-tumor efficacy and regulate TME more effectively by promoting dendritic cell maturation and enhancing CD8 + T cell infiltration ( 109 ). Although there is in vitro evidence that IFN-β inhibits tumor cell proliferation more effectively than IFN-α, no clinical trials have demonstrated its efficacy in cancer therapy ( 105 ).…”
Section: Cytokinesmentioning
confidence: 99%
“…Moreover, VEGF-A has also been demonstrated to directly promote the proliferation of VEGFR-2-expressing regulatory T cells in colon tumor-bearing mice. Accordingly, the treatment of CRC patients with the clinically approved VEGF-A-targeting antibody Bevacizumab resulted in a significantly reduced frequency of regulatory T cells in the peripheral blood, and the in vivo administration of a fusion protein consisting of an anti-VEGFR2 antibody and IFNα successfully enhanced the accumulation of CD8 + T cells in a murine colorectal cancer xenograft model [ 145 , 146 , 147 , 148 ].…”
Section: Conclusion and Targets Beyond Chemokines And Cytokinesmentioning
confidence: 99%